Effects of pore size and residual Ag on electrocatalytic properties of nanoporous gold films prepared by pulse electrochemical dealloying. (20th January 2015) - Chen, A.Y.; Wang, J.W.; Wang, Y.; Jia, Y.Q.; Gu, J.F.; Xie, X.F.; Pan, D.
Graphical abstract: The long-term potential cycling experiments prove that the NPG film with a pore size of 8 nm has an enhanced structural stability, resulting from the negligible residual Ag content. Highlights: Nanoporous gold (NPG) films were prepared by pulse electrochemical dealloying. Dissolution rate and surface diffusion control the formation of ultrafine pores. The size-dependence of electrocatalytic properties is explored. The NPG film with a pore size of 8 nm exhibits the best catalytic properties. The reason for this is the small pore size and few residual Ag content. Abstract: Nanoporous gold (NPG) films have emerged as promising electrodes in fuel cells and high-efficient energy conversion devices. The superior electrocatalytic properties of NPG films are closely related to the high specific surface area, and therefore controlled by the pore size. NPG films with ultrafine pores were produced by a pulse electrochemical dealloying method. The formation mechanisms of ultrafine pores are explored, concentrating on dissolution rate of Ag atoms and surface diffusion of Au atoms. The electrocatalytic activities of the as-prepared NPG films towards glucose are investigated by cyclic voltammetric measurements. The influences of pore size and residual Ag atoms on the electrocatalytic reaction, structural stability and catalyst poisoning are discussed. The NPG film with a pore size of 8 nm shows a significant increase of current intensity and a long-term cycle stability compared to the films with pore sizes of 4 and 20 nm. These special properties can be attributed to the ultrafine pore size and a small quantity of residual Ag atoms remaining in the NPG.